The Impact of Asymmetric Partial Feedback on Response‐Bias†. (11th July 2013) - Smillie, Luke D.; Quek, Boon‐Kiat; Dalgleish, Len I.
ABSTRACT For many decisions we make, we are more likely to receive feedback about some outcomes than about others, and thus we must operate under conditions of asymmetric partial feedback. In this paper, we examine the effects of asymmetric partial feedback on decision making across three experiments. Experiment 1 examines the effects of four partial feedback schedules on decision making in a single‐attribute auditory detection task. Experiment 2 examines these same schedules in the context of a simulated experiment in which virtual participants perform a multi‐attribute choice task. Experiment 3 then examines effects of one partial feedback schedule representative of a real‐world decision‐making domain (personnel selection) using an ecologically informed multi‐attribute choice task. All three experiments reveal that asymmetric partial feedback primarily impacts on response‐bias, a parameter of signal detection theory. These findings can be explained in terms of decision makers' attempts to maximize accuracy and the fact that shifts in response‐bias will, under partial feedback, produce misleading impressions of greater accuracy. Copyright © 2013 John Wiley & Sons, Ltd.